Eriomacrotergum flechtmanni n. gen. n. sp. (Trombidiformes: Eriophyidae), a new eriophyoid mite from the cupuaçu tree, Theobroma grandiflorum, from northern Brazil - Rodrigues, Daniela F.s.; Navia, Denise; Oliveira, Anibal R.; Ferragut, Francisco (Zootaxa, 2016)
A new eriophyid genus and species, tentatively placed in the Tegonotini, namely Eriomacrotergum flechtmanni n. gen. n. sp., is described from the Amazonian fruit tree cupuaçu Theobroma grandiflorum (Willd. Ex Spreng.) K. Schum. (Malvaceae), collected in northern Brazil. The new taxon presents a peculiar morphology in having a large opisthosomal plate and a very reduced prodorsal shield, with ocellar-like structures and scapular setae displaced laterally. Discussion on the most remarkable taxonomic traits is presented as well as similarities of the new genus with other Eriophyidae genera.